Normative-referenced values for health-related fitness among Czech youth: Physical fitness data from the study IPEN Adolescent Czech Republic - Rubín, Lukáš; Mitáš, Josef; Vorlíček, Michal; Dygrýn, Jan; Suchomel, Aleš; Lang, Justin J; Tomkinson, Grant R (Central European journal of public health, 2023)
OBJECTIVES: The aim of this study was to developed sex- and age-specific normative-referenced percentile values for health-related fitness among 12 to 18 years old Czech youth. METHODS: This study included cross-sectional data from 1,173 participants (50.7% boys) collected between 2013 and 2016. Participants were recruited from 32 elementary or secondary schools across eight cities located in the Czech Republic. Health-related fitness was objectively measured using both anthropometric (height, body mass, and sum of skinfolds) and performance (20-m shuttle run for cardiorespiratory endurance, modified push-ups for muscular strength/endurance, and V sit-and-reach for flexibility) tests. Sex- and age-specific normative values were calculated using the Lambda Mu Sigma method. Sex- and age-related differences in means were expressed as standardized effect sizes. RESULTS: Normative percentiles were tabulated and displayed as smoothed curves. Among boys, measures of health-related fitness generally increased with age, except for an age-related decline in the sum of skinfolds and a plateau in V sit-and-reach. Among girls, most measures of health-related fitness increased from age 12 to 16 years before stabilizing, except for the sum of skinfolds, which remained stable from age 12 to 18 years. The sex-related differences were large with boys having higher cardiorespiratory endurance and muscular strength/endurance than girls. Girls compared to boys had higher flexibility. CONCLUSIONS: This study presents the most up-to-date sex- and age-specific normative-referenced percentile values for health-related fitness among Czech youth. Normative values may be useful for fitness and public health screening and surveillance, for example, by helping to identify youth with low fitness who might benefit from a fitness-enhancing intervention.
Keywords: Female; zátěžový test; dítě; ženské pohlaví; průřezové studie; Physical Fitness; tělesná výkonnost; Adolescent; lidé; cvičení; Cross-Sectional Studies; Male; Czech Republic; Exercise Test; index tělesné hmotnosti; Česká republika; Child; mužské pohlaví; Exercise; Body Mass Index; mladiství; Humans